2018
DOI: 10.1002/cam4.1498
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a nine‐gene prognostic model for predicting overall survival of patients with endometrial carcinoma

Abstract: Endometrial carcinoma (EC) is the most common malignant tumor of the female genital tract in developed countries. The prognosis of early stage EC is favorable, but a subset faces high risk of cancer progression or recurrence. EC has a poor prognosis upon progression to advanced or metastatic stages. Therefore, our goal is to build a robust prognostic model for predicting overall survival (OS) in EC patients. In this study, 1571 genes were identified as being associated with OS based on genomewide expression pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 40 publications
(56 reference statements)
3
12
0
Order By: Relevance
“…Prior to this study, several prognostic models have been developed for EC based on gene signatures. Previously, we have proposed a nine‐gene model for survival prediction in EC, whose AUC values reached 0.82 and 0.676 in the training and validation datasets, respectively . A six‐gene signature devised by Wang et al also achieved good performance with AUC values of 0.841 and 0.722.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Prior to this study, several prognostic models have been developed for EC based on gene signatures. Previously, we have proposed a nine‐gene model for survival prediction in EC, whose AUC values reached 0.82 and 0.676 in the training and validation datasets, respectively . A six‐gene signature devised by Wang et al also achieved good performance with AUC values of 0.841 and 0.722.…”
Section: Discussionmentioning
confidence: 81%
“…Subsequently, multivariate Cox regression was applied to construct a prognostic model and remove any miRNAs that might not be independent factors in the model. For the gene model devised by our previous work, the risk score for each patient was computed using the list of nine genes ( SLC16A1‐AS1 , KDM4B , MAP2K5 , SYP , MPP1 , DLX4 , BOLA3‐AS1 , HOMEZ and STAP2 ) . For the prognostic model proposed by Wang et al, six genes ( PCSK4 , IHH , CTSW , LRRC8D , TNFRSF18 and CDKN2A ) were used to calculate the risk score for EC patient.…”
Section: Methodsmentioning
confidence: 99%
“…Here we show how multiple logistic regression can be used to model purity percentages with the advantage of being able to provide biologically relevant estimates, i.e., between 0 and 100% (Zhao et al, 2001). When further screening the most significant genes that contributed to the purity model with stepwise selection (Ying et al, 2018;Liu et al, 2019), we found the combination of collagen II and versican expression to be predictive, a relatively uncommon gene pair compared to the often studied gene expression ratios of collagen II:I and aggrecan:versican. The selection appears reasonable, with one chondrocyte marker, collagen II, and one perichondrium marker, versican, used in the model and being inversely related to each other.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reports have described the relationship between differentially expressed genes and various aspects of tumors, including tumorigenesis and prognosis [18][19][20]. However, a vast majority of genes implicated in playing a central role in predicting tumor prognosis are limited by certain factors, such as insu cient sample sizes.…”
Section: Discussionmentioning
confidence: 99%